Mutual consent in formation of financial contracts: a juristic analysis - Rahman, Md. Habibur; Amanullah, Muhammad; Osmani, Noor Mohammad (Asian Research Consortium, 2016)
As per the ruling of Islamic law, any kind of exchange in wealth, acquisition, possession, and the like will not be valid unless it is grounded on mutual consent of the contracting parties. This paper aims to study the issue of mutual consent and its function in the formation of contracts from the viewpoints of prominent Schools of Islamic law. This is a theoretical study and qualitative in nature. Classical sources of Islamic jurisprudence as well as understanding of the primary texts of Islamic law are used as the key tools in the process of drafting this paper. The paper discusses the various ways to express the consent along with the juristic analysis thereof. Also, this study explicates the practices lead to the invalidity of contracts due to lack of demonstration of assent. The paper concludes that no agreement will be considered sound in Islamic jurisprudence unless there is sufficient manifestation of mutual consent of parties concerned in the contract. ________________________________________________________________________________